Membrane Sphingolipids Regulate the Fitness and Antifungal Protein Susceptibility of Neurospora crassa - Huber, Anna; Oemer, Gregor; Malanovic, Nermina; Lohner, Karl; Kovács, Laura; Salvenmoser, Willi; Zschocke, Johannes; Keller, Markus A.; Marx, Florentine (Frontiers in Microbiology, 2019)
The membrane sphingolipid glucosylceramide (GlcCer) plays an important role in fungal fitness and adaptation to most diverse environments. Moreover, reported differences in the structure of GlcCer between fungi, plants and animals render this pathway a promising target for new generation therapeutics. Our knowledge about the GlcCer biosynthesis in fungi is mainly based on investigations of yeasts, whereas this pathway is less well characterized in molds. We therefore performed a detailed lipidomic profiling of GlcCer species present in N. crassa and comprehensively show that the deletion of genes encoding enzymes involved in GlcCer biosynthesis affects growth, conidiation and stress response in this model fungus. Importantly, our study evidences that differences in the pathway intermediates and their functional role exist between N. crassa and other fungal species. We further investigated the role of GlcCer in the susceptibility of N. crassa towards two small cysteine-rich and cationic antimicrobial proteins (AMPs), PAF and PAFB, which originate from the filamentous ascomycete Penicillium chrysogenum. The interaction of these AMPs with the fungal plasma membrane is crucial for their antifungal toxicity. We found that GlcCer determines the susceptibility of N. crassa towards PAF, but not PAFB. A higher electrostatic affinity of PAFB than PAF to anionic membrane surfaces might explain the difference in their antifungal mode of action.